Homicidal Paraquat Poisoning in Exhumed Case - Park, Sohyung; Jeong, Sujin; Lee, Han Young (Korean Journal of Legal Medicine, 2015)
Paraquat is a nonselective herbicide, but its lethal and toxic effects are well known. Although its chemical additives have an unpleasant taste, this can be shrouded in spicy foods or drinks with strong tastes, and some symptoms and signs of paraquat poisoning can be mistaken as natural disease. For this reason, it is not easy to consider the possibility of homicidal paraquat poisoning for a clinician or even for a forensic pathologist. We present a case of homicidal poisoning by paraquat with significant forensic findings from postmortem examination and with a review of relevant literature. KCI Citation Count: 0